Sensorimotor integration is affected by acute whole-body vibration: a coherence study - Lecce, E.; Nuccio, S.; Del Vecchio, A.; Conti, A.; Nicolò, A.; Sacchetti, M.; Felici, F.; Bazzucchi, I. (Frontiers in Physiology, 2023)
Several whole-body vibration (WBV) effects on performance have been related to potential changes in the neural drive, motor unit firing rate, and sensorimotor integration. In the present paper, motor unit coherence analysis was performed to detect the source of neural modulation based on the frequency domain.Thirteen men (25±2.1 years; Body Mass Index (BMI)= 23.9±1.3 kg•m 2 ; maximal voluntary force (MVF): 324.36±41.26 N) performed sustained contractions of the Tibialis Anterior (TA) at 10%MVF before and after acute WBV. The vibrating stimulus was applied barefoot through a platform to target the TA. High-Density surface Electromyography (HDsEMG) was used to record the myoelectrical activity of TA to evaluate coherence from motor unit cumulative spike-trains (CSTs).Mean coherence showed a significant decrease in the alpha and low-beta bandwidths (alpha: from 0.143±0.129 to 0.132±0.129, p=0.035; low-beta: from 0.117± 0.039 to 0.086±0.03, p=0.0001), whereas no significant changes were found in the other ones (p> 0.05). The discharge rate (DR) and the Force Covariance (CovF%) were not significantly affected by acute WBV exposure (p>0.05).According to the significant effects found in alpha and low-beta bandwidths, which reflect sensorimotor integration parameters, accompanied by no differences in the DR and CovF%, the present results underlined that possible neural mechanisms at the base of the previously reported performance Mechanical oscillations affect sensorimotor integration enhancements following acute WBV are likely based on sensorimotor integration rather than direct neural drive modulation.